Application cycles of a biostimulant on the development of coffee plants in nurseries - Ferrás-Negrín, Yusdel (2024)
Introduction. Search for alternatives with biostimulants that promote the growth and development of coffee plants in the nursery stage is very importance. Codafol 14-6-5, due to its composition, could be used as a nutritional alternative. However, the available information is insufficient to optimize its use. Objective. To evaluate the response of C. arabica plants to different cycles of foliar application of Codafol-14-6-5 during the nursery stage. Materials and methods. The research was conducted at Agro Forest Experimental Station nursery in Jibacoa, municipality of Manicaragua, Villa Clara province, Cuba. In a randomized design, three application cycles of Codafol 14-6-5 were studied 1) spraying on the plants when they reached the 3rd and 5th pair of leaves, 2) spraying on the 4th and 6th pair of leaves, 3) spraying from the 3rd to the 6th pair of leaves and 4) a control treatment (only water spray). Height, stem diameter, dry mass, and leaf area of ten plants per treatment taken at random were evaluated and efficiency indices were determined. Results. Spraying the biostimulant from the third to the sixth pair of leaves resulted average increases in height, stem diameter, dry mass and leaf area of 6.3%, 12.5%, 23.8% and 10.6%, respectively. This application cycle generally showed the highest efficiency indices in these evaluated variables. Conclusions. Applications of the biostimulant Codafol 14-6-5 promoted the development of C. arabica plants in the nursery stage. The application of the biostimulant from the 3rd to the 6th pair of leaves was the cycle that most comprehensively favored the growth of the coffee plants.